Parthian-India and Aksum: A geographical case for pre-Ezana early Christianity in Ethiopia - Rukuni, Rugare (HTS teologiese studies, 2020)
The narrative of Indian Christianity that is compositely based on Thomine tradition derives significantly from the reality of Parthian-India geo-economics and geopolitics. Although Aksumite trade and diplomatic visibility are a prevalent feature of the Greco-Roman imperial history in the BCE – CE era, the narrative regarding Ethiopian Christianity is a 4th-century CE reality. Ground is made to deduce the possibility of early Christianity akin to apostolic Christianity in Ethiopia as a consequence of similar circumstances in Parthian-India. So as to solidify the arguments and engage relevant data, document analysis complemented by cultural historiography and the archaeology of religion was implemented in this study. A deductive parallel review of Indian and Ethiopian geopolitical and geo-economics history within the context of Christianity as an emergent religion of the 1st century CE is implicative. The narrative of Ethiopia is completed when it is placed within its extensive geographic context, thereby consequently acknowledging its role within the Mediterranean world. Reference to India substantiates the logic of the argument and entails the possibility of the 1st to 3rd century Christian presence in Ethiopia.Contribution: The research highlights a revisionist history of Ethiopian Christianity thereby creating a new narrative for Jewish Christianity and Christian origins, a subject key to the field of theology.